Descriptive Study of Family Support for Hemodialysis Patients on Covid-19 Pandemic 2021 - Nimsi Melati; Iluh Sekar Ayu Dea Munararsi; Katarina Oktaviana Dongoran; Liviana Liviana; Luciana Renata; Yogi Januriswanti (Media Keperawatan Indonesia, 2022)
Patients with chronic renal failure undergoing hemodialysis (HD) need family support. This Covid-19 pandemic has brought changes to the HD service model by implementing health protocols and policies for limiting HD patient companions. This study was to determine the description of family support for hemodialysis patients during the COVID-19 pandemic. This study used a quantitative design with a descriptive method. The population in this study were all hemodialysis patients during the COVID-19 pandemic. A purposive sampling technique was used in this study and obtained a number of 53 respondents. The measuring instrument used in this study was a family support questionnaire shared online. The majority of respondents in this study were male (50.9%), aged >50 years (33.9%), married status (62.2%), higher education level (49%), and working in private employment (22.6%). Respondents get good family support (90.5%). The family support obtained by HD patients during the pandemic is in a good category. Good family support is very important for patients in the success of hemodialysis therapy.